Down-Regulation of the miRNA-200 Family at the Invasive Front of Colorectal Cancers with Degraded Basement Membrane Indicates EMT Is Involved in Cancer Progression - Emily L. Paterson (Neoplasia: An International Journal for Oncology Research, 2013)
Cancer progression is a complex series of events thought to incorporate the reversible developmental process of epithelial-to-mesenchymal transition (EMT). In vitro, the microRNA-200 family maintains the epithelial phenotype by posttranscriptionally inhibiting the E-cadherin repressors, ZEB1 and ZEB2. Here, we used in situ hybridization and immunohistochemistry to assess expression of miR-200 and EMT biomarkers in formalin-fixed paraffin-embedded human colorectal adenocarcinomas. In addition, laser capture microdissection and quantitative real-time polymerase chain reaction were employed to quantify levels of miR-200 in the normal epithelium, tumor core, invasive front, and stroma. We find that miR-200 is downregulated at the invasive front of colorectal adenocarcinomas that have destroyed and invaded beyond the basement membrane. However, regional lymph node metastases and vascular carcinoma deposits show strong expression of miR-200, suggesting this family of miRNAs is involved in the recapitulation of the primary tumor phenotype at metastatic sites. In contrast, adenomas and adenocarcinomas with intact basement membranes showed uniform miR-200 expression from the tumor core to the tumor-host interface. Taken together, these data support the involvement of EMT and mesenchymal-to-epithelial transition (MET) in the metastasis cascade and show that miR-200 is downregulated in the initial stages of stromal invasion but is restored at metastatic sites.